Emotions and the Micro-Foundations of Commitment Problems. (21st April 2017) - Renshon, Jonathan; Lee, Julia J.; Tingley, Dustin
Abstract: While emotions are widely regarded as integral to the "behavioral approach" to International Relations (IR), a host of fundamental problems have delayed the integration of affective influences into traditional models of IR. We aim to integrate affect by focusing on commitment problems, a body of work that contains strong theoretical predictions about how individual decision makers will and should act. Across two lab experiments, we use a novel experimental protocol that includes a psychophysiological measure of emotional arousal (skin conductance reactivity) to study how individuals react to changes in bargaining power. While we find support for one key pillar of IR theory—individuals do reject offers when they expect the opponent's power to increase—we also find that physiological arousal tampers with individuals' ability to think strategically in the manner predicted by canonical models. Our follow-up experiment mimics the elements of institutional solutions to commitment problems and finds support for their efficacy on the individual level. Our novel findings suggest that when individuals face large power shifts, emotional arousal short-circuits their ability to "think forward and induct backwards, " suggesting that emotionally aroused individuals are less prone to commitment problems.